2017
DOI: 10.1080/01612840.2017.1289287
|View full text |Cite
|
Sign up to set email alerts
|

“You Are Not Alone”Strategies for Addressing Mental Health and Health Promotion with a Refugee Women's Sewing Group

Abstract: Resettlement can be an uncertain time for refugees as they have often suffered life-threatening circumstances prior to flight from their countries, yet few resettlement programs screen for mental health. The purpose of this study was to pilot the Refugee Health Screener-15 (RHS-15) to assess mental health and the Pathways to Wellness intervention to identify internal and structural barriers affecting resettlement with a refugee women's sewing group. Community collaborations that create healthy social and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…Frequently, a perceived language barrier increased the feeling of isolation adding a sense of “dependency on other people and the inability to mix with people of other language backgrounds” [59]. The post-migration and resettlement phase are marked by uncertainties and appropriate social support can offer an integral approach to health and can improve quality of life [60]. This is especially important for pregnant women, where a lack of social support is a relevant prenatal risk factor that has negative effects on pregnancy outcomes [61].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, a perceived language barrier increased the feeling of isolation adding a sense of “dependency on other people and the inability to mix with people of other language backgrounds” [59]. The post-migration and resettlement phase are marked by uncertainties and appropriate social support can offer an integral approach to health and can improve quality of life [60]. This is especially important for pregnant women, where a lack of social support is a relevant prenatal risk factor that has negative effects on pregnancy outcomes [61].…”
Section: Discussionmentioning
confidence: 99%
“…Given the explorative nature of most of the investigations included, sustainability of interventions was limited after project completion, with many investigators bringing screening equipment or other supplies for use only during data collection. However, in at least one case, resources were available to continue health programs or provide interventions to participants or the community beyond the investigation [37].…”
Section: Post-investigation Supportmentioning
confidence: 99%
“…Newly relocated refugees in Finland showed a higher incidence of PTSD, somatization, and general distress than longer settled refugees (Mölsä et al, 2017). Salt and colleagues (2017) found that 80% of refugees participating in their health promotion intervention study demonstrated mental health distress that indicated the need for referral. When comparing mental health of newly arrived refugees with longer term refugees, Stingl et al (2017) reported that two-thirds of all refugees in Germany screened positive for mental health distress, and of those, 66% were newly arrived.…”
Section: Mental Health Of Refugeesmentioning
confidence: 99%